2016
DOI: 10.5213/inj.1632648.324
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of the Retrourethral Transobturator Male Sling After Transurethral Resection of the Prostate

Abstract: PurposeTo evaluate long-term outcomes of AdVance and AdVanceXP male slings in patients with persistent stress urinary incontinence (SUI) after transurethral resection of the prostate (TURP).MethodsA total of 18 consecutive patients received AdVance (n=14) or AdVanceXP (n=4) male sling implantation between 2007 and 2013. Continence was determined by pad use, 24-hour pad testing and validated questionnaires (International Consultation on Incontinence Questionnaire Short Form, ICIQ-SF). Quality of life was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…A successful outcome was described in 78% of the patients with divergent definitions of success (total continence, <2 g loss of urine, ≥50% pad reduction, and subjective improvement in continence) . Another study (not included in the above review), reported results of 15 post‐TURP patients treated with a male sling with a median follow‐up of 70 months . The outcome on continence after implantation of the male sling was improved with a greater than or equal to 50% pad reduction in 60% of the patients, including, 47% dry patients …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A successful outcome was described in 78% of the patients with divergent definitions of success (total continence, <2 g loss of urine, ≥50% pad reduction, and subjective improvement in continence) . Another study (not included in the above review), reported results of 15 post‐TURP patients treated with a male sling with a median follow‐up of 70 months . The outcome on continence after implantation of the male sling was improved with a greater than or equal to 50% pad reduction in 60% of the patients, including, 47% dry patients …”
Section: Discussionmentioning
confidence: 99%
“…Another study (not included in the above review), reported results of 15 post‐TURP patients treated with a male sling with a median follow‐up of 70 months . The outcome on continence after implantation of the male sling was improved with a greater than or equal to 50% pad reduction in 60% of the patients, including, 47% dry patients …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Es existiert lediglich eine Studie, die sich auf die Analyse der AdVancebzw. AdVanceXP-Schlinge nach TURP fokussierte [34]. Hierbei wurden insgesamt 18 konsekutive Patienten mit einem medianen Follow-Up von 70 Monaten eingeschlossen.…”
Section: Retrourethrale Transobturatorische Suspensionsschlingenunclassified